Human cardiac myosin light chain 4 (MYL4) mosaic expression patterns vary by sex - Tony Y. Wang (Nature Portfolio, 2019)
Abstract Sex disparities modulate cardiac function, although the proteins and mechanisms remain to be elucidated. We recently demonstrated a mosaic pattern of protein expression in the heart for over 100 proteins. Here we investigate one of these proteins, myosin light chain 4 (MYL4), which is important for contractile functions by increasing force production. We assayed the expression pattern of MYL4 across 756 ventricular myocardial samples from 668 individuals utilizing a semi-automated Cell Profiler method on five tissue microarrays (TMAs) of cardiac tissues across a diverse set of diseases. The percentage of MYL4 positive cells was significantly higher in male subjects independently across all five TMAs, regardless of disease state (p = 8.66e-15). Higher MYL4 expression was also modestly associated with hypertrophic cardiomyopathy (p = 6.3e-04). MYL4 expression did not associate with sudden cardiac death or other cardiomyopathies. This study demonstrates a new mosaic pattern of protein expression that underlies sex disparities in the human heart.